Le Secteur Informel En Tunisie - Dalbouchi, Rim (جامعة الوادي University of Eloued, 2025)
This article explores the informal sector in Tunisia, focusing on the KasserineTébessa border region, to analyze its role as a lever for resilience or a barrier to sustainable development. The study reveals that the informal sector, encompassing unregistered economic activities lacking social protection, employs approximately 36% of Tunisia’s workforce, exceeding 60% in marginalized regions like Kasserine. Accounting for nearly 30% of GDP, this sector thrives due to structural factors such as high unemployment, governance failures, regional inequalities, and economic crises. While it serves as a vital safety net for vulnerable populations, it also perpetuates precariousness, deprives the state of tax revenues, and distorts competition. The Kasserine-Tébessa case illustrates how informal cross-border trade has become a survival strategy, facilitated by geographic proximity and porous borders. In conclusion, the article questions the potential for transforming this sector into a model of regional integration, calling for policies that incorporate informal actors while addressing the root causes of marginalization.
The informal sector in Tunisia: a lever for development "Case of the Tunisian-Algerian border area: Kasserine-Tébessa"
مقال
Keywords: Informal sector; Tunisia; Kasserine-Tébessa; cross-border trade; economic resilience; regional disparities